SNPs and real-time quantitative PCR method for constitutional allelic copy number determination, the VPREB1 marker case - Costa Elena; Donnangelo Anita; Carminati Mario; Valaperta Rea; Rusconi Daniela; de Filippis Tiziana; Passeri Elena; Frigerio Marcello; Persani Luca; Finelli Palma; Corbetta Sabrina (BMC, 2011)
Abstract Background 22q11.2 microdeletion is responsible for the DiGeorge Syndrome, characterized by heart defects, psychiatric disorders, endocrine and immune alterations and a 1 in 4000 live birth prevalence. Real-time quantitative PCR (qPCR) approaches for allelic copy number determination have recently been investigated in 22q11.2 microdeletions detection. The qPCR method was performed for 22q11.2 microdeletions detection as a first-level screening approach in a genetically unknown series of patients with congenital heart defects. A technical issue related to the VPREB1 qPCR marker was pointed out. Methods A set of 100 unrelated Italian patients with congenital heart defects were tested for 22q11.2 microdeletions by a qPCR method using six different markers. Fluorescence In Situ Hybridization technique (FISH) was used for confirmation. Results qPCR identified six patients harbouring the 22q11.2 microdeletion, confirmed by FISH. The VPREB1 gene marker presented with a pattern consistent with hemideletion in one 3 Mb deleted patient, suggestive for a long distal deletion, and in additional five non-deleted patients. The long distal 22q11.2 deletion was not confirmed by Comparative Genomic Hybridization. Indeed, the VPREB1 gene marker generated false positive results in association with the rs1320 G/A SNP, a polymorphism localized within the VPREB1 marker reverse primer sequence. Patients heterozygous for rs1320 SNP, showed a qPCR profile consistent with the presence of a hemideletion. Conclusions Though the qPCR technique showed advantages as a screening approach in terms of cost and time, the VPREB1 marker case revealed that single nucleotide polymorphisms can interfere with qPCR data generating erroneous allelic copy number interpretations.